Features of civil legal status of minors and multidisciplinary approach to the protection of his property rights - Savina, Inga V. (Journal of the Belarusian State University. Law, 2019)
The article investigates the possible application of a multidisciplinary approach to the protection of property rights of children taking into account the peculiarities of their civil legal status. The article notes a special place of property rights in child rights system and lack of systematization of legislation in the sphere of childhood. Revealed that the protection of property rights of minors are objectively beyond the scope of one branch of law. The author proves the necessity of the development and adoption of the law оn property rights of minors, containing precise rights and guarantees.